Health consciousness, hedonic and eudaimonic motivations in green purchase intention among Generation Z - Andrés Acosta Aguinaga; Luciano Barcellos de Paula (Cogent Business & Management)
This study analyzes the determinants of green purchase intention among Generation Z consumers, considering health consciousness, environmental knowledge, and hedonic and eudaimonic motivations. Using a structural equation model (PLS-SEM), this study examines how these variables influence environmental attitudes, ultimately leading to green purchase intention. Both eudaimonic and hedonic motivations, along with health consciousness and environmental knowledge, play crucial roles in decision-making related to green products. These insights contribute to theory and practice by providing guidance for marketing strategies and public policies aimed at promoting sustainable consumption, particularly by emphasizing emotional and health-related factors.